2015
DOI: 10.18805/lr.v38i6.6733
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield response of chickpea to Rhizobium inoculation: productivity in relation to interception of radiation

Abstract: To test the taxonomy of medical Astragalus penduliflorus complex and specific status of A. petrovii, eleven accessions (covering four species) in China were sampled herein for an AFLP study. A total of 346 informative polymorphic bands from eight primers pairs were obtained, dendrogram was generated using UPGMA analysis. The results indicated A. membranaceus is more morphologically and generically diverse than A. mongholicus on the populational level. Both of them and the former species A. minhensis were degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…In support of this, the late maturing genotypes reached the peak of radiation interception a week after the early and medium maturing genotypes suggesting a longer LAD in the late genotypes. The effect of management practices on LAD in chickpea has been reported previously at the site of the current study (Ogola, 2015). Earlier, Anwar et al (2003) attributed the variation in total intercepted radiation amongst chickpea genotypes to a similar genotypic variation in days to physiological maturity.…”
Section: Intercepted Radiationsupporting
confidence: 74%
See 3 more Smart Citations
“…In support of this, the late maturing genotypes reached the peak of radiation interception a week after the early and medium maturing genotypes suggesting a longer LAD in the late genotypes. The effect of management practices on LAD in chickpea has been reported previously at the site of the current study (Ogola, 2015). Earlier, Anwar et al (2003) attributed the variation in total intercepted radiation amongst chickpea genotypes to a similar genotypic variation in days to physiological maturity.…”
Section: Intercepted Radiationsupporting
confidence: 74%
“…Although we did not measure canopy size directly in this study, it is clear from equation 7, famously known as the Monsi and Saeki (1953) equation, and Figure 2a & b that canopy size was greater in early sowing compared to the control and late sowing Gautam et al, 2019). Moreover, early sowing recorded higher peak values of Fi and also reached peak values of Fi almost 14 days later than the control and late sowing, suggesting that the early sowing recorded greater leaf area duration (Bhattacharya, 2018;Ogola, 2015).…”
Section: Intercepted Radiationmentioning
confidence: 65%
See 2 more Smart Citations
“…Similarly, Maleki et al (2009) conducted a pot experiment in Iran and reported higher yield where rhizobial inoculation was done as compared to uninoculated control. Furthur, Ogola (2015) from South Africa reported increase in the grain yield to the tune of 7.9% with Rhizobium inoculation in a clayey and slightly acidic soil.…”
Section: Symbiotic Parametersmentioning
confidence: 99%